A case of bullous pyoderma gangrenosum with endometrial adenocarcinoma - Asmae Abdelmouttalib; Najoua Ammar; Mariame Meziane; Nadia Ismaili; Leila Benzekri; Karima Senouci (Our Dermatology Online, 2022)
Pyoderma gangrenosum (PG) is a reactive non-infectious inflammatory dermatosis falling under the spectrum of neutrophilic dermatoses. PG is generally classified into four types: ulcerative, pustular, bullous, and vegetative. Among them, bullous PG is known to be a rare type [1]. Herein, we report a case of bullous PG in a seventy-year-old female with a medical history significant for endometrial adenocarcinoma diagnosed five years previously with total hysterectomy and bilateral adnexectomy. Several years later, the patient presented a strangulated eventration treated with musculo-aponeurotic suture. Afterward, she presented purulent and hemorrhagic blisters on the abdominal wall. They were quickly progressive, painful, and necrotic with ragged, undermined edges and violaceous/erythematous borders. An abdominopelvic CT scan showed a large collection in the anterior abdominal wall without intraabdominal extension. Initially, the lesions were considered secondary to superinfection of the abdominal wall and were treated with antibiotics, drainage, and necrosectomy. As the lesions failed to improve, the patient was transferred to the dermatology department and a skin biopsy was performed, confirming the diagnosis of pyoderma gangrenosum (Fig. 1). Although systemic corticosteroids were administered at a dose of 1 mg/kg/day with the lesions starting to heal (Fig. 2), the patient died in less than two months. PG may precede, coexist, or follow diverse systemic diseases. The bullous variety is usually associated with hematologic disorders and is considered a predictor of hematological malignancies, such as acute or chronic myeloid leukemia that indicates characteristic pathophysiology specific to bullous PG. Despite being a well-recognized condition, PG is often diagnosed not early enough. Such a diagnosis should be actively considered when assessing ulcers, as prompt treatment may prevent the complications of prolonged systemic therapy, delayed wound healing, and scarring.